2009
DOI: 10.1097/tp.0b013e3181af7d84
|View full text |Cite
|
Sign up to set email alerts
|

HLA-C Matching and Liver Transplants: Donor-Recipient Genotypes Influence Early Outcome and CD8+KIR2D+ T-Cells Recuperation

Abstract: This study confirms the benefit of HLA-C allele matching on early liver transplant outcome and shows that donor HLA-C heterozygosis influences the alloresponse of C1 and C2 homozygous patients and the recuperation of CD3CD8KIR2D T cells, suggesting an involvement in liver graft tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 56 publications
8
29
1
Order By: Relevance
“…The bias of KIR2D ϩ NK cell number observed at the end of the follow-up period in C2/C2 homozygous patients experiencing AR also contrasted with the higher CD8 ϩ KIR2D ϩ T-cell expansion in patients without AR independent of the HLA-C genotype. Altogether, differences in the KIR2D ϩ NK and T cells, at least in part, may be responsible for the differences in the frequency of AR previously described in C1 and C2 homozygous recipients [5]. Thus, our data suggest that in liver recipients, the recuperation of KIR2D ϩ NK cells would be subrogated to the concomitant presence of C2 ligands and early AR, whereas that of CD8 ϩ KIR2D ϩ T cells appear to be less restricted to C-ligands and linked to a better early liver graft success.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The bias of KIR2D ϩ NK cell number observed at the end of the follow-up period in C2/C2 homozygous patients experiencing AR also contrasted with the higher CD8 ϩ KIR2D ϩ T-cell expansion in patients without AR independent of the HLA-C genotype. Altogether, differences in the KIR2D ϩ NK and T cells, at least in part, may be responsible for the differences in the frequency of AR previously described in C1 and C2 homozygous recipients [5]. Thus, our data suggest that in liver recipients, the recuperation of KIR2D ϩ NK cells would be subrogated to the concomitant presence of C2 ligands and early AR, whereas that of CD8 ϩ KIR2D ϩ T cells appear to be less restricted to C-ligands and linked to a better early liver graft success.…”
Section: Discussionmentioning
confidence: 92%
“…However, there are few studies regarding the peripheral blood lymphocytes that express KIR receptors in organ transplantation [5,34,35]. Therefore, the intent of this work was to study both NK and CD8 ϩ T-cell populations expressing KIR2D receptors before and following liver transplantation to ascertain their possible connection with the early transplant outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 HLA-C matching is associated with lower rates of rejection in liver and renal transplants, however, its association with graft survival has yet to be established. 11,12 Our study found no association between graft survival or early reported rejection in HLA-C matching. Similar to other reports in solid organ transplant and bone marrow transplant, our study did not find associations between HLA matching at the DQ locus and graft outcomes or early rejection.…”
Section: Discussionmentioning
confidence: 42%
“…9 HLA-C matching has been associated with better outcomes in stem cell transplantation, renal, and liver transplantation. [10][11][12] The effect of HLA-C matching has remained relatively unexplored in heart transplantation. HLA-DQ locus is present on antigen presenting cells and is involved in presenting self and foreign proteins to the immune system.…”
Section: Introductionmentioning
confidence: 99%